Ciência, magia e filosofia no processo de ensino-aprendizagem da matemática: uma introdução histórica sobre o Teorema de Pitágoras - Cano, Marco Aurelio Munhoz (2007)
The present dissertation focuses some relations between the influence of Pythagoras in Old Greece and the historical approach of the Pythagorean Theorem worked by Mathematics teachers during the elementary and high schools, following the National Curricular Parameters (PCNs) exigencies and giving emphasis to the connected aspects to science, magic and philosophy in the teaching/learning process of Mathematics. We know that the Mathematics did not evolve of a linear form and logically organized and was developed following different ways in several cultures, where the Mathematics pattern today accepted and used in the present work have originated with the Greek civilization, in approximately the period of 700 B.C. to 300 A.C. Although the historical Pythagoras existence has raised doubts for many, it s important to recognize that his works, activities and concepts throughout the years, even surrounded by myths and legends, had exerted deep influences in the Greek culture. At the first moment of the work, it was necessary a historical and legendary inventory on the Pythagoras life and work. At the second moment, we analyze four didactic books in the historical context and collate these analyses with the curricular proposals, specially the National Curricular Parameters (PCNs). We had as a target public the students of 5. and 7. series of elementary school (particular net S.C.S.), 3. series of high school (municipal net S.C.S.) and students from the National Service of Industrial Learning (SENAI Almirante Tamandaré S.B.C.). With that experiment, it was possible to evidence some advantages in relation to the adopted approach concerning to the importance of the historical aspects in the teaching / learning process of Mathematics. Nobody will contest that the Mathematics teacher must have knowledge of his subject. But the transmission of this knowledge through education depends on his understanding of how this knowledge was originated, of which the main motivations for its development and which were the reasons of its presence in the school curricula. To detach these facts is one of the main objectives of the Mathematics History. (Ubiratan D. Ambrósio)